Saints and Heretics: The Fight against the Infidel in the Religious Festivals of the Kingdom of Toledo between 1565 and 1622 - Sanz Baso, Ángela (Eikón / Imago, 2020)
In light of the recent research on religious alterity that has been flourishing in recent years, we want to make a new contribution on otherness in the Kingdom of Toledo during the 16th and 17th centuries. This article deals with analyzing the image of the "other" (Muslims, Moors, Turks, Protestants, etc.) in the religious festivals of Madrid, Alcalá de Henares and Toledo held between 1565 and 1622. Through them we intend to deepen and contributing to give renewed vision in the analysis of the ephemeral art produced in the canonizations, beatifications and translations of relics, which allows us to understand how the vision of the enemy evolved and shaped through the messages transmitted by the ruling classes.